God against the gods : the history of the war between monotheism and polytheism - Kirsch, Jonathan, 1949- (New York : Penguin Compass, 2005)
In this ... book, [the author] explores the final struggle between monotheism and polytheism in the ancient world, a war that was fought by a series of charismatic, visionary but also violent monarchs in the name of the One True God - an Egyptian pharaoh, a Jewish king, and two Roman emperors. Contrary to the conventional wisdom of Judaism, Christianity, and Islam, the world of classical paganism was not steeped in sin. In fact, [according to the author], religious liberty and diversity were core values of classical paganism, and it was monotheism that introduced the terrors of true belief, including holy war, martyrdom, inquisitions, and crusades.-Dust jacket.
Prologue: The everlasting fire -- bk. 1. The god that failed: Against all the gods of Egypt : a young pharaoh's experiment in monotheism and why it failed. What did pagans do? : the case against classical paganism, and why it was wrong. Terror and true belief: The Jewish king who reinvented the faith of ancient Israel. Confessors and traitors: pagans and Christians go to war in ancient Rome -- bk. 2. War of God against the gods: "In this sign, conquer": the curious encounter of Christ and Constantine in the struggle for the Roman crown. The harlot in the bishop's bed : the war within the Christian church over the divinity of Christ. The ruler of the whole world : the investion of the totalitarian state by the first Christian Emperor of Rome. The orphans of Macellum : The Christian prince who survived a blood purge and struggled for the restoration of paganism. The secret pagan : Gods, empresses, and Julian's unlikely rise to the imperial throne. "Behold, the rivers are running backwards" : the pagan counterrevolution of the Emperor Julian. The handless scribe : the price of victory of the only true god.
Includes bibliographical references (p. [315]-321) and index.
Keywords: Monotheism -- History; Polytheism -- History